On recently described Procridinae taxa from the Volga Region (Lepidoptera: Zygaenidae) - Konstantin A. Efetov; Gerhard M. Tarmann (SHILAP, 2022)
The systematic position of the recently described taxa: Jordanita (Roccia) scintillosa Zolotuhin, 2020, J. (R.) smaragdonna Zolotuhin, 2020, and Adscita (Adscita) albanica accola Zolotuhin & Nedoshivina, 2020, are discussed. J. scintillosa and J. smaragdonna are considered to be synonyms of Jordanita (Roccia) paupera (Christoph, 1887) and A. albanica accola is synonymised with the nominotypical Adscita albanica (Naufock, 1926). Moreover, some notes on the book “Zygaenoid moths (Lepidoptera, Zygaenoidea) of the Middle and Lower Volga Region” are presented.